Upaya Pemenuhan Nutrisi Pada Ibu Hamil Trimester Kedua Untuk Menambah Ukuran Lila - Indah Wijayanti, Fajar, Sulastri, S.Kp., M.Kes (2017)
Background : Pregnancynis a period in which one woman to save an embryo or fetus within her body. Human pregnancy occurred 40 weeks starting time is gravida pregnant, and the man called the embriyos in her uterus (early weeks) the fetus until birth. Someone women who are pregnant for the first time called primigravidae (gravida 1) and in women who have never beenpregnant are called gravida 0 based on the measuremnt report LILA, national preverensi KEK among wus was 14,8% with the number of about 30 million ople.Objective : Can handle arm circumference in pregnant women in cordance with the standards of nursing care. Methods : The method used is descriptive in Ny. V with case study approach is to perform nursing care at the start of the sment,intervention, implementation, and evaluation. Result : After 3 days of nursing care during home visits diagnosis appears in Ny. V is the lack of penghetahuan associated with less information (of nutrition to increase the size of LILA). Conclusion : Nursing problems that occur on the client is resolved in part so that intervention should still be continued.